2022
DOI: 10.3390/app122111092
|View full text |Cite
|
Sign up to set email alerts
|

ACapMed: Automatic Captioning for Medical Imaging

Abstract: Medical image captioning is a very challenging task that has been rarely addressed in the literature on natural image captioning. Some existing image captioning techniques exploit objects present in the image next to the visual features while generating descriptions. However, this is not possible for medical image captioning when one requires following clinician-like explanations in image content descriptions. Inspired by the preceding, this paper proposes using medical concepts associated with images, in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…BLEU score ImageSem [29] 25.7% "Show, Attend and Tell" [16] 43.7% Attention-based encoder-decoder [9] 28.7% Our proposal 40.29%…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BLEU score ImageSem [29] 25.7% "Show, Attend and Tell" [16] 43.7% Attention-based encoder-decoder [9] 28.7% Our proposal 40.29%…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by this, we extend our proposed model [9] for the ImageCLEFmedical 2021 [10], [11] by adding an explainability module. We present therefore, an attention-based encoderdecoder model for medical image captioning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies worldwide have reported additional challenges, including (1) a fourfold increase in the workload of radiologists from 2006 to 2020 [8]; (2) the potential decrease in the accuracy of CT image analysis due to the increased workload [9]; (3) a minimum of 30 min required by radiologists to write an interpretation report after analyzing CT images [10]. Therefore, there is a growing effort in research for the image captioningbased automation of medical image analysis to assist physicians by reducing the time required for radiologists to write interpretation reports and streamlining the diagnostic and treatment processes [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used MIMIC-CXR [18], Open-I [19], MS-COCO [20], and ImageCLEF [21] datasets, which are publicly available training datasets for various types of medical images, as well as chest X-ray images. Reference [11] designs three encoders to extract the following feature vectors: (1) visual feature vector (using VGG-16 [22]): vector representation for medical images, (2) semantic feature vector (using VGG-16): vector representation for the classification results and information about the imaging method of medical images, (3) caption vector (using NLTK [23]): vector representation for captions about medical images. These encoder vectors are concatenated and fed into a decoder, which is LSTM (long short-term memory [24]), to generate texts through a beam search method.…”
Section: Introductionmentioning
confidence: 99%